Communicating customer value in sustainable fashion: Strategies and implications review for ethical consumerism - Ikhma Zurani; Genny Gustina Sari; Mohd Rendy Samudra; Fibriyani Nur Aliya (Science, Technology, and Communication Journal, 2026)
The fast fashion industry, with its penchant for consumerism, trash, and greenhouse gas emissions, is primarily responsible for environmental damage. Slow fashion is a movement that aims to promote more responsible consumerism through its emphasis on sustainable practices, ethical manufacture, and long-lasting design. In order to express sustainable ideals to consumers in the fashion industry, this study examines successful sustainability communication tactics. As a result of being impacted by honesty, equity, and repurposed goods, slow fashion customers place a premium on ethical business methods, environmental consciousness, and classic style. Constructal level theory, meanwhile, shows that while abstract messages reach more people, sustainability-conscious consumers are more receptive to concrete ones. However, despite the continued ineffectiveness of organisational green marketing, attitudes towards green products among Generation Z are driving sustainable behaviour. The environmental problems caused by rapid fashion necessitate more stringent regulations and consumer education, particularly in Vietnam. The findings of this study can help fashion industry stakeholders and policymakers tackle sustainability issues.